Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Solve [tex]\( x^2 - 8x - 9 = 0 \)[/tex].

Rewrite the equation in the form [tex]\( x^2 + bx = c \)[/tex].

[tex]\[ x^2 + \square x = \square \][/tex]


Sagot :

To solve the quadratic equation [tex]\(x^2 - 8x - 9 = 0\)[/tex], we need to rewrite it in the form [tex]\(x^2 + bx = c\)[/tex].

Here's a step-by-step solution:

1. Start with the given equation:
[tex]\[ x^2 - 8x - 9 = 0 \][/tex]

2. Move the constant term to the right side of the equation. This isolates the terms involving [tex]\(x\)[/tex] on the left side:
[tex]\[ x^2 - 8x = 9 \][/tex]

In this form, you can see that [tex]\(b = -8\)[/tex] and [tex]\(c = 9\)[/tex],

Therefore, the equation in the form [tex]\(x^2 + bx = c\)[/tex] is:
[tex]\[ x^2 + (-8)x = 9 \][/tex]

So, the final rewritten form is:
[tex]\[ x^2 + \boxed{-8}x = \boxed{9} \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.